Simvastatin-Loaded Nanostructured Lipid Carriers as Topical Drug Delivery System for Wound Healing Purposes: Preparation, Characterization, and In Vivo Histopathological Studies - Seyedeh Maryam Mousavi-Simakani; Amir Azadi; Nader Tanideh; Navid Omidifar; Parisa Ghasemiyeh; Soliman Mohammadi-Samani (Tabriz University of Medical Sciences, 2023)
Purpose: Simvastatin, a 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitor, is a commonly used drug to reduce total cholesterol and low-density lipoprotein (LDL) levels. Furthermore, several mechanisms showed the wound-healing potential of statins, especially simvastatin. Simvastatin is a lipophilic drug, therefore, it has low water solubility with limited skin permeability potential. In this regard, nanostructured lipid carriers (NLCs) were recruited as novel topical drug delivery systems to enhance skin adhesion and film formation, maintain skin integrity, sustain the release of simvastatin, and prolong simvastatin skin deposition to help pressure ulcers healing and regeneration. Methods: NLCs were fabricated using the solvent diffusion evaporation technique. Drug loading, in vitro drug release, and morphological assessment on the optimized formulation were considered. Furthermore, in vivo effect of simvastatin-loaded NLCs gel on pressure ulcer healing was assessed using a rat skin model. Histopathological assessments were compared with conventional simvastatin gel and drug-free NLCs gel. Results: Simvastatin-loaded NLC with an average diameter of 100 nm was considered as the optimum formulation. According to the results entrapment efficiency of simvastatin within the NLCs was about 99.4%. Drug release studies revealed sustained drug release from NLCs in which about 87% of the drug was slowly released during 48 hours. Animal study results confirmed that simvastatin-loaded NLCs gel has better efficacy on pressure ulcers and could significantly reduce inflammation, and promote skin regeneration compared to both drug-free NLCs and conventional simvastatin gels. Conclusion: Simvastatin-loaded NLCs with an average particle size of 100 nm would be a promising novel topical drug delivery system with sustained drug release potential for pressure ulcer treatment.